Analysis of Hydrogeochemical Characteristics of Tunnel Groundwater Based on Multivariate Statistical Technology. (6th December 2021) - Peng, Chen; Liu, Yuanming; Chen, Huiyu; Yuan, Qiaowei; Chen, Qingzhi; Mei, Shilong; Wu, Zhonghu
Abstract : Following tunnel excavation, which is influenced by hydraulic fracturing and geological structure, a series of hydrochemical reactions occur in the karst aquifer, which has a significant impact on groundwater hydrology and the earth process. Based on five sets of 38 samples collected in the Tongzi Tunnel in 2020 and 2021, the main geochemical processes and water quality conditions of the karst aquifer system during tunnel construction were revealed by multivariate statistical analysis and graphical methods. The results showed that water-rock action is the main mechanism controlling groundwater chemistry in the study area; HCO3 -, Ca 2+, and Mg 2+ are associated with the widely distributed carbonate rocks in the study area. SO4 2- is derived from gypsum and sulfate rocks and special strata, which are another important source of Ca 2+ . Sodium-containing silicates and reverse cation exchange as the causal mechanisms of Na + whereas F - is derived from fluorite. According to the mineral saturation index calculations, the dissolution and precipitation of minerals such as alum, gypsum, calcite, dolomite, and salt rock have an important influence on the main chemical components in water. The 38 samples were subjected to cluster analysis, and the results could be classified into seven categories. The representative clusters 1, 3, and 5 were selected for principal component analysis. Clusters 1 and 5 of groundwater represent weathering, dissolution, and ion exchange of carbonate and sulfate rocks and are closely related to the lithologic limestone, limestone intercalated with carbonaceous mudstone, carbonaceous mudstone, and coal-measure strata in the aquifer. Cluster 3 is dominated by upper surface river water and characterizes the geochemistry in natural water bodies dominated by the dissolution of carbonate, sulfate, and salt rocks. Finally, groundwater quality is mostly found in Class IV, with NO3 - and F - being the main contaminants in the water.